Long-term effects on function, health-related quality of life and work ability after structured physiotherapy including a workplace intervention. A secondary analysis of a randomised controlled trial (WorkUp) in primary care for patients with neck and/or back pain - Malin H. Forsbrand; Aleksandra Turkiewicz; Ingemar F. Petersson; Charlotte Post Sennehed; Kjerstin Stigmar (Taylor & Francis Group, 2020)
Objective: To study the long-term effects of a workplace intervention in addition to structured physiotherapy regarding self-reported measures in patients with acute/subacute neck and/or back pain. Design: WorkUp - a cluster-randomised controlled trial in 32 primary care centers in Sweden, from January 2013 through December 2014 (ClinicalTrials.gov ID: NCT02609750). Intervention: Structured physiotherapy with the workplace dialogue 'Convergence Dialogue Meeting' (CDM), conducted by the treating physiotherapist as an add-on. Reference group received structured physiotherapy. Subjects: Adults, 18-67 years (mean 43.7, standard deviation (SD) 12.2), 65.3% women with acute/subacute neck and/or back pain who had worked ≥4 weeks past year, considered at risk of sick leave or were on short-term sick leave (≤60 days) were included (n = 352). Outcome measures: Self-reported function, functional rating index (FRI), health-related quality of life (EQ-5D-3L) and work ability (Work Ability Score, WAS) at 12 months follow-up. Results: The mean differences in outcomes between intervention and reference group were; −0.76 (95% confidence interval (CI): −2.39, 0.88; FRI), 0.02 (95% CI: −0.04, 0.08; EQ-5D-3L) and −0.05 (95% CI: −0.63, 0.53; WAS). From baseline to 12 months, the intervention group improved function from 46.5 (SD 19.7) to 10.5 (SD 7.3) on FRI; health-related quality of life from 0.53 (SD 0.29) to 0.74 (SD 0.20) on EQ-5D and work ability from 5.7 (SD 2.6) to 7.6 (SD 2.1) on WAS. Conclusion: Despite a clinically relevant improvement over time, there were no significant differences in improvement between groups, thus we conclude that CDM had no effect on self-reported measures in this study.Key points In earlier analysis of the primary outcome (work ability measured by absenteeism) in this trial, a positive effect was found when the workplace intervention 'Convergence Dialogue Meeting' (CDM) was added to structured physiotherapy for patients with neck or back pain. By contrast, in this new analysis of secondary outcomes (self-reported function, health and perceived work ability), there was no added effect of CDM above structured physiotherapy alone, although patients in both the intervention and reference group improved over time. The addition of CDM to physiotherapy is therefore justified by its specific effect on behavior (work absence) rather than any effect on clinical outcomes.